Semiotika dalam Metode Analisis Karya Seni Rupa - Pangeran Paita Yunus; Muhammad Muhaemin (Universitas Bumigora, 2022)
Fine art is one of the artifacts that are present as a result of human behavior and human actions that are driven by motivation in their thoughts and feelings. Therefore, a work of art is not something isolated but is an element of a system so that the meaning contained in it is systemic as well. This means that the meaning of a work of art can be determined by the system, by the work of art itself, and by the humans who make the work of art, or who associate physical elements from the environment with certain meanings. This has become the object of theoretical study and is systematically analyzed by semiotics by relying on the sign as the main concept. Fine art in the study of semiotics is not only limited to a theoretical framework, but also as a method of analysis. For example, in fine art analysis, Peirce's theory of triangle meaning consisting of a sign, object, and interpretant is one theory that can be applied.